Centro Studi e Documentazione
Founded in 1971. Initially directed to track and field, then turned also to physical education, other sports, and related sciences (anatomy, physiology, psychology, etc.). It is a cultural association and has a sport library with books, reviews, magazines, newspapers and a splendid photo archives. Library is open free from Monday to Friday from 10 a.m. to 1 p.m.; closed in July and August. No loans. Yes photocopies. Possible help for researches. Study Center has published for seven years a review of track and field techniques and now have a lot of other enterprises.